Generals in politics - "Khan, Mohammad Asghar" (Ghaziabad, 1983)
This book covers the following topics related to Pakistan the army enters politics; how Bangladesh was born; Rebirth of democracy; the guardians of the law; Pakistan's second general election; Dialogue with a difference; the army digs in; The real martial law; Prospects for the future etc.
Keywords: Politics